Site-specific mechanical properties of the human great saphenous vein: Cadaveric comparisons among the thigh, knee, and lower leg harvest sites. (July 2022) - Arima, Takahiro; Otsuka, Shun; Mitsuoka, Hiroki; Nakano, Takashi; Naito, Munekazu; Ishibashi, Hiroyuki
Background: This study aimed to determine site-specific mechanical properties of the great saphenous vein (GSV) harvested from various sites in the same cadaver. Methods: GSV samples were harvested from three sites: the thigh, knee, and lower leg. The thickness and diameter of the samples were measured, and the tensile test was performed to measure stiffness and Young's modulus. Results: The stiffness of the GSV harvested from knees in the longitudinal direction was lower than those from other sites, whereas the stiffness of the GSV harvested from the lower leg in the circumferential direction was lower than that from the thigh. Conclusions: The GSV has site-specific mechanical properties. Thus, in addition to morphological evaluations such as echo and computed tomography in preoperative graft surgical evaluations, knowledge of the mechanical properties at each site can improve the patency rate and prevent aneurysmal expansion.